Evaluation of the Accuracy of Different Apex Locaters with 45° Apical Root Resorption - Ahmed I Al-Jobory; Mohammed Ayad Taha; Mohammed Jabbar Atyiah (University Library System, University of Pittsburgh, 2024)
Aim: This study was aimed to calculate the working length (WL) of permanent teeth with simulated 45° resorption of the apical part of the root using four electric apex locaters (EALs): NSK, Woodpecker III, Woodpecker V, and Eighteeth. Methods: Twenty maxillary anterior single-rooted teeth were removed. Following tooth preparation to offer access to the root canal and replicate the 45° apical root resorption, each tooth underwent a microscope-assisted working length determination process. The four apex locaters measured each individual tooth and calculated electronic working lengths. Results: No discernible change existed between all four apex locater devices. Conclusion: NSK, Woodpecker III, Woodpecker V, and Eighteeth provide virtually the same measurement for 45 apical root resorption in single rooted teeth.